Clinical trials in dermatology - K. Torre; M. Shahriari (Wolters Kluwer, 2017)
Clinical trials are the backbone of modern day medicine. Randomized, double-blinded, placebo-controlled studies are critical for advancement in medicine and dermatology. Skin conditions such as psoriasis and atopic dermatitis are among the most common health problems in the United States. Clinical trials can provide treatments that not only offer objective improvements in clinical disease status but also subjective improvements in the quality of life of patients who are afflicted with the disease. In this article, we discuss the processes and resources of a clinical trials unit and the challenges that can be encountered during the study process. It is critical to engage in clinical trials to treat patients most effectively with new and innovative therapies that are rooted in trial-validated, evidence-based medicine. Keywords: clinical trials, design, randomized, controlled, placebo, double-blinded